Gas-dust flow separation in a centrifugal inertial dust catcher in terms of ecological-economic approach - Ya. V. Chistyakov; A. A. Makhnin; A. V. Nevsky (Тонкие химические технологии)
A methodology of designing an ecological-economic high-performance centrifugal inertial dust catcher-classifier is proposed allowing a description of the separation of solid particles from an air flow. The particles enter the separation zone - a space where their separation from the air flow occurs.